2006
DOI: 10.1021/ja063710z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Palladium(II) Catalysis:  A Highly Efficient and Chemoselective Cross-Coupling Method for Carbon−Carbon Bond Formation under Base-Free and Nitrogenous-Ligand Conditions

Abstract: We report herein the development of a general and mild protocol of oxygen-promoted Pd(II) catalysis resulting in the selective cross-couplings of alkenyl- and arylboron compounds with various olefins. Unlike most cross-coupling reactions, this new methodology works well even in the absence of bases, consequently averting undesired homo-couplings. Nitrogen-based ligands including dimethyl-phenanathroline enhance reactivities and offer a highly efficient and stereoselective methodology to overcome challenging su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
87
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(97 citation statements)
references
References 51 publications
6
87
1
3
Order By: Relevance
“…The N ligands clearly proved to be superior. The commercially available and inexpensive neocuproine [17] (7 b) combined excellent diastereoselectivity with the low formation of regioisomers (< 2 %). PdCl 2 was found to be the best Pd source and switching from Pd to Ni as the catalyst resulted in a deterioration of the d.r.…”
mentioning
confidence: 99%
“…The N ligands clearly proved to be superior. The commercially available and inexpensive neocuproine [17] (7 b) combined excellent diastereoselectivity with the low formation of regioisomers (< 2 %). PdCl 2 was found to be the best Pd source and switching from Pd to Ni as the catalyst resulted in a deterioration of the d.r.…”
mentioning
confidence: 99%
“…Initially,t his reactionw as carried out by using 2.0 equivalents of diethylp yrocarbonate (2) [15,19] in the reaction (Table 1, entry 22), and found that the yield was less than the result under an argon atmosphere (Table 1, entry 20). It was also found that the yield was loweri nt he presence of ac ertain amount of water [12] ( Table 1, entry 23).…”
mentioning
confidence: 99%
“…4) ersetzt wurde. Die NLiganden erwiesen sich als deutlich überlegen, vor allem Neocuproin [17] (7 b), das kommerziell erhältlich und kostengünstig ist und eine herausragende Diastereoselektivität mit nur geringer Regioisomerenbildung (< 2 %) verbindet. bevorzugten cis-1,3-disubstituierten Cyclohexanderivate [18] mit guten Ausbeuten und hervorragenden Diastereoselektivitäten erhalten (d.r.…”
unclassified